ANALYSIS OF ARTISTIC TEXT IN ASSOCIATIVE ASPECT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article analyzes the artistic text based on the methods of associative linguistics, which are considered an independent branch of anthropocentric linguistics, and groups the associative units within the text.